Not Enough Time or a Low Priority? Barriers to Evidence‐Based Practice for Allied Health Clinicians. Issue 4 (October 2014) - Harding, Katherine E.; Porter, Judi; Horne‐Thompson, Anne; Donley, Euan; Taylor, Nicholas F.
<x xml:space="preserve">Abstract</x> Introduction Evidence‐based practice (EBP) is a key principle in the delivery of effective and high‐quality health care. Existing research suggests that allied health professionals are generally supportive of EBP but rarely participate in activities associated with EBP. Methods This mixed‐method study used 8 focus groups of allied health professionals and managers and a questionnaire of all participants to explore the attitudes and barriers to EBP in a large metropolitan health service. Qualitative data were analyzed using a thematic analysis of focus group transcriptions. Questionnaire data were analyzed descriptively. Results Fifty clinicians and 10 managers across 7 allied health disciplines participated in the study. The questionnaire identified that clinicians have a positive attitude but low participation in EBP. Qualitative data revealed that EBP was not highly valued by clinicians and managers or viewed as a core component of clinical care, with activities directly related to maintaining patient flow viewed as higher priorities. Lack of skills and resources and difficulty associated with implementing evidence into practice were further barriers. Discussion Achieving higher uptake of EBP among allied health clinicians requires a cultural shift, placing higher value on these activities despite the challenging context of constant pressures to increase patient flow. Addressing EBP through small group projects rather than considering it to be an individual responsibility may be more acceptable to both clinicians and managers, with added benefits of peer support for both evaluating evidence and translation into practice.